At Home with Ivan Vladislavić An African Flaneur Greens the Postcolonial City - Gaylard, Gerald (Taylor & Francis, 2023)
At Home With Ivan Vladislavić is the first comprehensive analysis of the works of Ivan Vladislavić. Bringing a flaneur's "internal GPS" to postcolonial Johannesburg, Vladislavić established a critical sense of home via an intimate knowledge of geography and history. This sense of belonging can have positive ecological effects as we tend to protect what we know. The flaneur's deep word hoard also helped him to develop a minimalist style, which was not only a means of living sustainably in the city, but in its humour and close attention to detail a way to make greening the city more of a joy than a duty. In this way, Vladislavić created a culture of sustainability.